PENGARUH KOMPENSASI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DENGAN BUDAYA ORGANISASIONAL SEBAGAI MEDIASI (STUDI DI PUSKESMAS EKS KAWEDANAN PATI) - 11.42.02.0082, Ardhian Sucahyati (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study has an ain reveal the influence of compensation and communication toward the employeeâs performance with organization culture as a mediation (Study in Puskesmas / Health Centre eks Kawedanan Pati). This study has been done toward 163 civil servant in eks kawedanan Pati. Sampling technique uses Purposive Sampling and taking an employee who has been working at least 4 years about 121 person. The statistic technique which has been used is a validity test with reliability test matrix component with alfa cronbach, double analytical regrestion, t test and r2 test with adjusted r square. The result of the study is known that compensation influencing toward organization culture. Communication has a positive influence toward organization culture. Compensation has a positive influence toward employeeâs performance in puskesmas exs kawedanan Pati. Communication has an influence toward employeeâs performance in puskesmas exs kawedanan Pati. Organization culture has a positive influence toward employeeâs performance in puskesmas exs kawedanan Pati. Organization culture doesnât bring mediation to the compensation influence with the employeeâs performance in puskesmas exs kawedanan Pati. Organization culture doesnât bring mediation t the communication influence toward employeeâs performance in puskesmas exs kawedanan Pati. Keyword : Compensation, Communication, Culture Organization and Performance